(untitled) (LEARNing Landscapes, 2010)
In this commentary the author examines the exciting role that education has played—and still plays—in her life. She discusses the joy of attending law school where legal cases and rulings piqued her thirst for knowledge. Later, she reiterates Jane Jacobs’ cautionary warning about education being replaced by "certification" and students being degraded to mere "consumers" of an educational product. She concludes by stressing the importance of protecting and valuing education for its own sake.